Future and Organization Studies: On the rediscovery of a problematic temporal category in organizations - Wenzel, Matthias; Krämer, Hannes; Koch, Jochen; Reckwitz, Andreas (Organization studies, 2020)
Even though organizational activities have always been future-oriented, actors’ fascination with the future is not a universal phenomenon of organizational life. Human experience of the future is a rather young product of modernity, in which actors discovered the indeterminacy of the future, as well as their abilities to ‘make’ and, in part, even control and de-problematize it through ever-more sophisticated planning practices. In this essay, we argue that actors have recently ‘rediscovered’ the future as a problematic, open-ended category in organizational life, one that they cannot delineate through planning practices alone. This, we suggest, has been produced through a pluralization of what we refer to as ‘future-making practices’, a set of practices through which actors produce and enact the future. Based on illustrations of the experienced problematic open-endedness of the future in prevalent discourses such as climate change, digital transformation and post-truth politics, we invite scholars to explore future-making practices as an important but under-appreciated organizational phenomenon.